A new phenolic series of indenopyridinone as topoisomerase inhibitors: Design, synthesis, and structure-activity relationships. Issue 18 (1st October 2018) - Shrestha, Aarajana; Park, Seojeong; Jang, Hae Jin; Katila, Pramila; Shrestha, Ritina; Kwon, Youngjoo; Lee, Eung-Seok
Graphical abstract: Highlights: Phenolic series of indenopyridinone were synthesized. SAR study was performed by comparing topo inhibitory and anti-proliferative activity. para- Phenolic group at 2- and/or 4-position of indenopyridinones is important. Compound12 acted as DNA-intercalative potent topo IIα inhibitor. Indenopyridinone as potential scaffold for anticancer activity. Abstract: DNA Topoisomerase IIα (topo IIα) is one of the most effective therapeutic targets to control cancer. In an effort to develop novel and effective topo IIα targeting anti-proliferative agent, a phenolic series of indenopyridinone and indenopyridinol were designed and prepared using efficient multi-component one pot synthetic method. Total twenty-two synthesized compounds were assessed for topo I and IIα inhibition, and anti-proliferation in three different human cancer cell lines. Overall structure-activity relationship study explored the significance of meta- phenolic group at 4-position and para- phenolic group at 2- and/or 4-position of indenopyridinone skeleton for strong topo IIα-selective inhibition and anti-proliferative activity against human cervix (HeLa) and colorectal (HCT15) cell lines. Compound12 with excellent topo IIα inhibition (93.7%) was confirmed as a DNA intercalator that could be a new promising lead to develop effective topo IIα-targeted anticancer agents.